Transcriptome analysis based on RNA-seq of common innate immune responses of flounder cells to IHNV, VHSV, and HIRRV - Kim, Kwang Il; Lee, Unn Hwa; Cho, Miyoung; Jung, Sung-Hee; Min, Eun Young; Park, Jeong Woo (PLOS ONE, 2020)
Viral hemorrhagic septicemia virus (VHSV) and hirame rhabdovirus (HIRRV) belong to the genus Novirhabdovirus and are the causative agents of a serious disease in cultured flounder. However, infectious hematopoietic necrosis virus (IHNV), a prototype of the genus Novirhabdovirus, does not cause disease in flounder. To determine whether IHNV growth is restricted in flounder cells, we compared the growth of IHNV with that of VHSV and HIRRV in hirame natural embryo (HINAE) cells infected with novirhabdoviruses at 1 multiplicity of infection. Unexpectedly, we found that IHNV grew as well as VHSV and HIRRV. For successful growth in host cells, viruses modulate innate immune responses exerted by virus-infected cells. Our results suggest that IHNV, like VHSV and HIRRV, has evolved the ability to overcome the innate immune response of flounder cells. To determine the innate immune response genes of virus-infected HINAE cells which are commonly modulated by the three novirhabdoviruses, we infected HINAE cells with novirhabdoviruses at multiplicity of infection (MOI) 1 and performed an RNA sequencing-based transcriptome analysis at 24 h post-infection. We discovered 12,500 unigenes altered by novirhabdovirus infection and found that many of these were involved in multiple cellular pathways. After novirhabdovirus infection, 170 genes involved in the innate immune response were differentially expressed compared to uninfected cells. Among them, 9 genes changed expression by more than 2-fold and were commonly modulated by all three novirhabdoviruses. Interferon regulatory factor 8 (IRF8), C-X-C motif chemokine receptor 1 (CXCR1), Toll/interleukin-1 receptor domain-containing adapter protein (TIRAP), cholesterol 25-hydroxylase (CH25H), C-X-C motif chemokine ligand 11, duplicate 5 (CXCL11.5), and Toll-like receptor 2 (TLR2) were up-regulated, whereas C-C motif chemokine receptor 6a (CCR6a), interleukin-12a (IL12a), and Toll-like receptor 1 (TLR1) were down-regulated. These genes have been reported to be involved in antiviral responses and, thus, their modulation may be critical for the growth of novirhabdovirus in flounder cells. This is the first report to identify innate immune response genes in flounder that are commonly modulated by IHNV, VHSV, and HIRRV. These data will provide new insights into how novirhabdoviruses survive the innate immune response of flounder cells.